Molecular Characterisation of Extended Spectrum Beta-Lactamase-Producing Escherichia Coli in Selayang Hospital, Malaysia. - Yusof, Rusmah (2011)
Infection caused by extended spectrum beta-lactamases E. coli (ESBLs-E.coli) strains, which are resistant to many classes of antibiotics, is an important nosocomial infection and one of the public health concerns in this country. The molecular characteristics of these organisms in the local setting were insufficiently documented. The recent increase in diversity of the ESBL types and the prevalence of emerging CTX-M types worldwide in the hospital setting and also in the community, warrants a study to improve detection protocols. Although most CTX-M types preferentially hydrolyse cefotaxime and are therefore resistant to cefotaxime rather than ceftazidime, currently the appearance of CTX-M types capable of hydrolysing both ceftazidime as well as cefotaxime at a high level of efficiency has made phenotypic recognition difficult. Confusion arises when some CTX-M types are also capable of hydrolysing ceftazidime instead of cefotaxime. Therefore, this study was conducted to portray a preliminary genetic characterisation as well as the clonal relatedness of ESBL-producing E. coli from a tertiary hospital in Malaysia, and to resolve the difficulty in the identification of ESBL types based on phenotypic traits. The alternative approach using molecular methods to specifically detect CTX-M types was investigated. ESBL types, from a total of sixteen isolates obtained over the months of January to December 2006 from Hospital Selayang, were characterized by PCR and DNA sequencing based on genes encoding for blatem, blashv and blaCTX-M, respectively. Clonal relatedness of the isolates was determined by MLST and plasmid profiling. The CTX-M β-lactamase gene produced by E.coli was detected by a membrane assay based on an optimised dot blot hybridisation technique. All strains that were phenotypically determined to be ESBL were found to carry at least one of the ESBL genes. The prevalence of blaCTX-M and blaTEM genes was 81.3% and 75%, respectively, while 12.5% carried the blaSHV gene. This study demonstrated that CTX-M types are dominant strains. This is parallel to the worldwide trend where CTX-M types have overtaken the global dominance of traditional TEM- and SHV-types. In view of the confusion surrounding blaCTX-M detection based on phenotypic hydrolysing of ceftazidime and cefotaxime, the molecular characterisation of CTX-M was further elucidated. Further determination of CTX-M nucleotide and deduced protein sequences showed that 46% were found to be CTX-M-15, 31% were CTX-M-14, 15% were CTX-M-69 and 8% were CTX-M-3. The emergence of CTX-M-15, a particularly common type, was also revealed in this study. This study also illustrated MLST typing as the first molecular surveillance tool developed for local ESBL E. coli. The finding revealed the presence of several new ESBL E. coli strains with new strain type (ST) numbers assigned from the global MLST database published on the Web. A dendrogram which was developed based on the MLST STs revealed clustering of strains isolated from a local hospital setting based on allelic profiles. A rapid genotypic-based method for detection of CTX-M illustrated that a CTX-M biotin-labelled probe, designed from consensus DNA sequences of local CTX-M variants of E. coli, were sensitive and specific for the respective E. coli target genes. The developed probe was able to detect local CTX-M variants as well as a number of CTX-M control strains. The optimised membrane assay, using the colorimetric detection technique, was capable of completing the assignment within one working day without specific molecular equipments. This finding suggests that with further independent validation, the detection of CTX-M types by dot blot assay can be potentially used in Diagnostic Clinical Microbiology Laboratories to replace current phenotypic detection methods. In essence, the confusion surrounding the phenotypic detection of CTX-M warrants resolution since these strains are more dominant than blaTEM or blashv. The rapid genotypic-based method investigated in the study consistently detected the CTX-M gene in all phenotypic-positive CTX-M strains. In addition, the differentiation of CTX-M types was also elucidated through molecular approaches. The establishment of the MLST-typing method is another highlight of this research since this is the first MLST-typing study for local E. coli ESBL stains. The rapid CTX-M genotypic detection assay is very noteworthy since the assay provided an easy, fast and reliable method of detecting various CTX-M genes from local ESBL-producing E. coli as well as control strains from Canada and France.